«Зеленый шатер» Л. Улицкой и «Бесы» Ф.М. Достоевского - САБО, ТЮНДЕ (SlavVaria, 2021)
L. Ulitskaya’s The Big Green Tent and F.M. Dostoevsky’s Demons. L. Ulitskaya does not usually mention Dostoevsky’s name when she speaks of writers who have influenced her art. Nevertheless, Dostoevsky’s influence can be clearly seen in her works. The study examines how Ulitskaya’s novel The Big Green Tent relates to Dostoevsky’s Demons at different levels: the plot’s structure, metaphors, system of characters and their literary activity.